Ressignificação dos discursos no cinema: dialogismo e recepção crítica em Tudo sobre minha mãe, de Pedro Almodóvar - Fernandes, Marcelo de Lima (2019)
This work aims to conduct a film analysis on Pedro Almodóvar’s All about my mother (1999) by identifying the dialogic relations (BAKHTIN, 2003; STAM, 1992) that are inherent to the filmic text. We believe that these discursive interactions serve as core points that both produce and revise social meanings, thus revealing the connections that exist between fiction and society. Therefore, we study primarily the dialogic game established between Almodóvar’s film and Joseph Mankiewicz’s All about Eve (1950); Tennessee William’s play A streetcar named Desire (1947) and its film adaptation, directed by Elia Kazan; Federico Garcia Lorca’s play Blood wedding (1933); and melodrama. The narratological categories of space (LINS, 1976) and character (ROSENFELD, 2002; SALES GOMES, 2002) are also contemplated, as is the movies’ critical reception (BRAGA, 2006) – we consider film criticism as another player in this dialogic web that is built around the movie